The Effects of Iot- New Features on Security and Privacy (Trinity Journal of Management, IT & Media (TJMITM), 2022)
IoT technology is drawing a very important communication line between  individuals. It’s providing how of effective communication. Additionally to the  current, it’s conjointly creating people’s life higher by providing how for good  home systems, good agriculture systems and even additional good systems that  folks want. The maximum amount as this technology is sweet as attackers attempt  to exploit it during a unhealthy thanks to attack the IoT systems and build edges  of innocent sensitive knowledge and data. This makes it necessary to develop ways  and techniques that might defend IoT systems. That successively defend people’s  sensitive info. Security and privacy of IoT systems became a challenge and a very  important a part of IoT systems. Security and privacy problems take issue in their  danger level. Some attacks are additional dangerous than different attacks. Also,  attacks take issue in their supply some attacks are internal and different attacks are  external. Attacks may be completely different however their negative have an effect  on is that the same and vary within the dangerous level. This paper explains about  the privacy and security, threats, attack etc.
Keywords: Internet of things (IOT); IOT features; privacy and security